Pengembangan Lembar Aktivitas Siswa (LAS) berbasis Penemuan Terbimbing pada Materi Lingkaran untuk Kelas VIII SMP - Yulia Ulfa Harahap; Ratri Isharyadi; Arcat (Karoteh Utama, 2022)
This study aims to produce a valid guided discovery-based Student Activity Sheet (LAS) on circle material. Research and development (Research and Development) is the type of research used. The development procedure used in this research follows the 4-D development model, which is modified into 3-D, consisting of defining, designing and developing. The instrument used in this study was a validation questionnaire sheet. The validation questionnaire sheet consists of didactic, content, language, and display aspects. Data analysis was carried out by calculating the average of each aspect at this validation stage. Based on the validity test of the guided discovery-based LAS, which three validators have carried out with several revisions and improvements, the average score of the guided discovery-based LAS validation results is 3.36, with a very good category. So it can be concluded that LAS based on guided discovery is valid.